Application of Soft Squirrel-Cage Induction Motor Starting, Braking and Retarded Speed Operation for Crane Travel Mechanisms - B. I. Firago; D. S. Vassilyev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers an improvement of crane equipment operation, particularly, its travel mechanisms  at the expense of updating currently widely applied electric drives with squirrel-cage induction motors. The authors propose to use a pulse voltage regulator based on IGBT transistors with additional function of quasi-frequency control ability as a soft starter which has higher technical-economic indices in comparison with existing thyristor starters and prove its application by the results of their investigations. Application of such device in  electric drives of crane travel mechanisms where there is no need to carry out a technological speed regulation, allows to make soft starting, soft braking and accurate stoppage of an electric drive at the cost of  squirrel-cage induction motor transition to retarded speed prior to stoppage which is ensured by quasi-frequency motor control.